A root-mean-square CMOS power detector with robustness to temperature variation and low power consumption of 1.91mW - Chang, Jin (Nanyang Technological University, 2022)
With the great development of mobile communication technology, transmit power control module is becoming an indispensable part of mobile systems. As the core part of transmit power control module, RF power detector needs to be studied. Based on the basic principle of CMOS circuit, this thesis designs an RF power detector with a power supply of 1.8V. The design scheme proposed has the characteristics of low power consumption (1.91mW), low temperature drift below than 0.6 dB and large detection range of 20 dB. The whole circuit is composed of three parts, a Root-Mean-Square detection module, a fully differential amplifier module, and a single-ended output amplifier module. An RF input signal firstly passes the RMS module, which uses the voltage-current conversion characteristic of saturated MOSFET. In this module there is capacitance that acts as a filter. It can filter out components of the signal that we don't need. So, the signal is converted to the squared dc current by this block. The output current of the RMS module is fed into the differential amplifier module, which converts the current to voltage with its load resistor. And single-ended output amplifier module finally converts the differential signal to single-ended voltage. The signal passes through these three modules in turn, and the final power detection effect can be realized. Its working frequency is in the range from 1GHz to 20GHz. Global Foundry 130nm BiCMOS process is used for the power detector design.